Keberhasilan siswa kompetisi sains madrasah nasional dalam menyelesaikan masalah matematika terintegrasi Islam pada materi segitiga - Rofiki, Imam; Alghar, Muhammad Zia (Pusat Studi Pengembangan Pembelajaran Matematika, 2024)
This study aims to describe the success of Madrasah Science Competition students at the national level in solving Islamic integrated math problems on triangle material. The research was conducted qualitatively on 5 students at the Madrasah Tsanawiyah (MTs) / equivalent level who participated in the Madrasah Science Competition (KSM) at the national level and successfully solved Islamic integrated mathematics problems on triangle material. The research instrument was a triangle problem given during the National KSM in 2023. The results showed the existence of two strategies that lead to success, namely success with complex mathematical proficiency and success with simple mathematical proficiency. In addition, the strategy of registering students with simple mathematical proficiency was found, namely listing from smallest to largest and listing from largest to smallest. This research contributes to science in the form of a description of students' success in solving triangle problems with various solution strategies. The results of this study are useful as guidelines in designing learning designs or tools that lead to student success in solving Islamic integrated mathematics problems.